Development of Student Worksheets for Basic Chemical Laws Based on Problem Based Learning Phase E of Senior High School - Jannah, Miftahul; Fitri, Bali Yana (Edukimia, 2025)
Information obtained from the results of interviews with chemistry teachers that there is no LKPD that uses the problem based learning model. Based on the summative value of students on the material of basic chemical laws, it can be concluded that students' understanding of the material of basic chemical laws is still low. This study aims to develop and analyze the validity and practicality of teaching materials in the form of LKPD basic chemical laws based on problem based learning phase E of SMA. The type of research conducted is Educational Design Research (EDR) with the Plomp model. The data obtained are processed using the Aiken's V formula. The study was conducted at the Department of Chemistry, FMIPA UNP and SMA Pembangunan Laboratorium UNP. The validation results show that LKPD has a validity value of 0.90 and a practicality value for teachers of 93.75% and students of 88.6%. The results of the study indicate that the LKPD basic chemical laws based on problem based learning that was developed is valid and practical.